De nuevo sobre la Garcineida - Pérez González, Maurilio (Cuadernos de Filología Clásica. Estudios Latinos, 2004)
In the light of recent “critical’ reviews published in ALMA, Euphrosyne, Speculum and other scientific journals. The author reconsiders some of his own opinions and reaffirms others that appear in his study and critical edition of the Garcineida